The TWEAK/Fn14 pathway is required for calcineurin inhibitor toxicity of the kidneys. Issue 7 (6th February 2018) - Claus, Meike; Herro, Rana; Wolf, Dennis; Buscher, Konrad; Rudloff, Stefan; Huynh‐Do, Uyen; Burkly, Linda; Croft, Michael; Sidler, Daniel
Abstract : Calcineurin inhibitor toxicity (CNT) is a frequent occurrence in transplanted renal grafts and autochthone kidneys from patients undergoing long‐term treatment with calcineurin inhibitors, notably cyclosporin A (CsA) and tacrolimus. Here, we show an indispensable role of the tumor necrosis factor superfamily (TNFS) molecule TNF‐related weak inducer of apoptosis (TWEAK) (TNFSF12) in the pathogenesis of acute CNT lesions in mice. A deficiency in TWEAK resulted in limited tubulotoxicity after CsA exposure, which correlated with diminished expression of inflammatory cytokines and reduced intraparenchymal infiltration with immune cells. We further identified tubular epithelial cells of the kidney as major targets of CsA activity and found that Fn14 (tumor necrosis factor receptor superfamily 12A), the receptor for TWEAK, is a highly CsA‐inducible gene in these cells. Correlating with this, CsA pretreatment sensitized tubular epithelial cells specifically to the pro‐inflammatory activities of recombinant TWEAK in vitro. Moreover, injection of rTWEAK alone into mice induced moderate disease similar to CsA, and rTWEAK combined with CsA resulted in synergistic nephrotoxicity. These findings support the importance of tubular epithelial cells as cellular targets of CsA toxicity and introduce TWEAK as a critical contributor to CNT pathogenesis. Abstract : The authors provide evidence for the indispensable role of TWEAK in acute calcineurin inhibitor nephrotoxicity (CNT) and introduce TWEAK's receptor Fn14 as a potential marker for CNT.